Preventive forensic audit and its role in the corruption case of the District University in 2019 (2020)
This essay aims to show the role that preventive forensic auditing plays as a necessary tool in the processes of analysis and detection of fraud and corruption, contributing to their detection, as well as, the strengthening of control measures in these possible cases. The above, through a theoretical and regulatory framework, national and international. These serve as a guide and organize for the audit process and so that it is executed with quality and truthfulness, obtaining evidence that supports the fraud. The essay analyzed the case of corruption and fraud that occurred at the Universidad Distrital, in the Idexud ́s dependency, executed by public officials of this Institute, they incurred at crimes against the public administration. The above, want to show the forensic auditing process carried out by the Fiscalía General de la Nacion, identifying the role of the forensic audit, the use of tools and regulations, which is carried out in the development of the investigation in the case of the Universidad Distrital.